The water of life and death: A brief economic history of spirits - Lara Cockx; Giulia Meloni; Johan Swinnen (Katholieke Universiteit Leuven, LICOS Centre for Institutions and Economic Performance, 2019)
Spirits represent around 50% of global alcohol consumption. This sector is much less studied than other alcohol beverages such as wine or beer. This paper reviews the economic history of spirits and analyses recent trends in the spirits markets. The technology to produce spirits is more complex than for wine or beer. Distillation was known in ancient Chinese, Indian, Greek and Egyptian societies, but it took innovations by the Arabs to distil alcohol. Initially this alcohol was used for medicinal purposes. Only in the middle ages did spirits become a widespread drink and did commercial production and markets. The Industrial Revolution created a large consumer market and reduced the cost of spirits, contributing to excess consumption and alcoholism. Governments have intervened extensively in spirits markets to reduce excessive consumption and to raise taxes. There have been significant changes in spirits consumption and trade over time. Over the past 50 years, the share of spirits in global alcohol consumption increased from around 30% to around 50%. In the past decades there was strong growth in emerging markets, including in China and India. The spirits industry has concentrated, but less so than e.g. the brewery industry. Recent developments in the spirits industry include premiumization, the growth of craft spirits and the introduction of terroir for spirits.
Keywords: 330; Spirits; distillation technology; globalization and convergence of alcohol preferences; alcohol and health; alcohol regulations; craft and industry concentration